Actinomycosis of Cecum Associated with Entamoeba Infection Mimicking Perforated Colon Cancer - Deniz Eren Böler; Cihan Uras; Süha Göksel; Mehmet Karaarslan (Case Reports in Gastrointestinal Medicine)
Actinomycosis is a granulomatous disease caused by Actinomyces that mimics other intra-abdominal pathologies especially neoplasms. Correct diagnosis can be rarely established before radical surgery. On the other hand Entamoeba infection affects a considerable number of people worldwide. To our knowledge only one case has been reported to be affected by both organisms. We report a man who has been operated for a mass in the cecum mimicking a perforated colon cancer. Abdominal CT revealed a mass with features of an invading neoplasm. After radical surgery, definitive pathology revealed that the mass was due to actinomycosis associated with Entamoeba infection. The postoperative period was uneventful and the patient was on long-course antibiotherapy. It is important to consider actinomycosis especially in patients with intra-abdominal masses with unusual aggressiveness to prevent unnecessary surgery. However, surgery can be unavoidable especially in the presence of complicated disease or high index of suspicion for malignancy.